Menjelajahi Keragaman Budaya Islam: Sebuah Studi Literature Review - Istiqomah Istiqomah; Moh. Soehadha (Madania: Jurnal Ilmu-Ilmu Keislaman, 2023)
Diverse efforts to promote Islamic understanding, practice, and values in various cultural contexts are essential to strengthening and preserving Islamic culture within Muslim societies. The objective of this study is to analyze Islamic culture using a methodical literature review. The refined data is comprised of 929 documents from the Scopus database. However, based on a predetermined evaluation of quality, only 20 of the selected articles were eligible after data analysis. The study's findings indicate that the interaction between Islam and local culture in each country is heavily influenced by its historical and geographical context. Local culture existed in the majority of Muslim nations prior to the advent of Islam. In certain instances, Islam adapts to the local culture, while in others, the local culture adapts to Islam. Then, cultural Islam can provide a framework for comprehending who Muslims are in terms of the formation of social identity. Islam provides guidelines for dress, speech, and social conduct that are consistent with Islamic doctrines. Moreover, a number of policies can be implemented to strengthen and preserve Islamic culture in Muslim societies. Development of the Islamic culture industry, promotion of Islamic culture, protection and preservation of Islamic historical sites, quality education, and public policy are some of the methods.